A randomized controlled trial to examine the impact of a multi-strain probiotic on self-reported indicators of depression, anxiety, mood, and associated biomarkers - Kylie E. Walden; Jessica M. Moon; Anthony M. Hagele; Leah E. Allen; Connor J. Gaige; Joesi M. Krieger; Ralf Jäger; Petey W. Mumford; Marco Pane; Chad M. Kerksick (Frontiers in Nutrition, 2023)
ObjectiveTo examine the efficacy of supplementing with a multi-strain probiotic (MSP) on changes associated with mood, anxiety, and neurotransmitter levels.MethodIn a randomized, double-blind, placebo-controlled fashion, 70 healthy men and women (31.0 ± 9.5 years, 173.0 ± 10.4 cm, 73.9 ± 13.8 kg, 24.6 ± 3.5 kg/m2) supplemented with a single capsule of MSP (a total daily dose of 4 × 109 live cells comprised of a 1 × 109 live cells dose from each of the following strains: Limosilactobacillus fermentum LF16, Lacticaseibacillus rhamnosus LR06, Lactiplantibacillus plantarum LP01, and Bifidobacterium longum 04, Probiotical S.p.A., Novara, Italy) or a maltodextrin placebo (PLA). After 0, 2, 4, and 6 weeks of supplementation and 3 weeks after ceasing supplementation, study participants completed the Beck Depression Inventory (BDI-II), State-Trait Anxiety Inventory (STAI), and Leiden Index of Depression Sensitivity (LEIDS-R) questionnaires and had plasma concentrations of cortisol, dopamine, serotonin, and C-reactive protein determined.ResultsBDI, STAI, and total LEIDS-R scores were reduced from baseline (p < 0.05) with MSP supplementation after 4 and 6 weeks of supplementation and 3 weeks after supplementation while no changes (p > 0.05) were reported in PLA. When compared to PLA, MSP scores for state anxiety, trait anxiety, and LEIDS-R (hopeless, aggression, rumination, and total score) were significantly lower (p < 0.05) after supplementation. Plasma serotonin concentrations in MSP were increased from baseline after 6 weeks of supplementation and 3 weeks after ceasing supplementation. No changes (p > 0.05) in plasma dopamine, C-reactive protein, or cortisol concentrations were observed between groups.ConclusionMSP supplementation resulted in widespread improvements in several questionnaires evaluating mood, anxiety, and depression in young, healthy men and women. MSP supplementation increased serotonin increased after 6 weeks of MSP supplementation with no change in dopamine, C-reactive protein, or cortisol.Clinical trial registrationhttps://classic.clinicaltrials.gov/ct2/show/NCT05343533, NCT05343533.